ANALISIS PENGARUH LITERASI KEUANGAN SYARIAH TERHADAP KEPUTUSAN MENGGUNAKAN PRODUK PERBANKAN SYARIAH (Studi pada Mahasiswa Program Studi Perbankan Syariah FEB UNISMA) - Ahmad Basori; Maslichah Maslichah; M Cholid Mawardi (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
This study aims to determine the effect of Islamic financial literacy on decisions to use Islamic banking products in students of the Islamic Banking Study Program FEB UNISMA. The location of this research was carried out on students of the Islamic Banking Study Program FEB UNISMA. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to students of the Islamic Banking Study Program FEB UNISMA who were selected by purposive sampling. Determination of the number of samples using the Slovin formula and the results obtained were 100 respondents. Data were analyzed using simple regression analysis and determination test. Based on the results of data analysis, the results of the t-test indicate that Islamic financial literacy has a significant and positive effect on purchasing decisions and has an effect on decisions to use Islamic banking products for students of the Islamic Banking Study Program FEB UNISMA. Furthermore, the results of the t test show that Islamic financial literacy partially has a significant and positive effect on the decision to use Islamic banking products. The results of the determination test show that the percentage is 9.9%, where the decision to use the product can be influenced by Islamic financial literacy. Furthermore, in this study, the data collection method can be continued by paying attention to the willingness of respondents, follow-up to fill out, so that when given a questionnaire, they can immediately fill in the data properly.